Series and elementary algebra (2) plus complex numbers [disket] (Derbyshire, Eng. : Topclass Technology, 1989)
Module 2.1. Quadratic equations (1) -- Module 2.2. Quadratic equations (2) -- Module 2.3. Inequalities and curve sketching -- Module 2.4. Permutations and combinations -- Module 2.5. Complex numbers -- Module 2.6. Simple uses of De Moivre's theorem